'Cooling out the marks': the ideology and politics of vocational education in an age of austerity. Issue 2 (3rd April 2017) - Leach, Tony
Abstract: As cuts in public-sector funding continue to affect the lives and careers of public-sector workers in the UK, and in other countries, there are added pressures on educational establishments to equip students with the knowledge and skills for employability, sustainable employment and career development in an employment marketplace characterised by neo-liberal principles and practices. In this new era of austerity, the empirical research for this paper is focused on the career experiences of graduate employees working in the public sector. The paper examines the contested ideology and politics of vocational education. Specifically, it argues that the policy-driven discourse on vocational education informs a 'cooling out' process that deflects attention away from structural weakness in the economy, and disavows the impact of major changes in labour-market conditions and in employer–employee relationships. This cooling out process, whereby individuals are made morally responsible to make something of their lives, in contexts where opportunities to do so are increasingly reduced, perpetuates ideological fantasies of individual aspiration and opportunity that amount to a form of 'cruel optimism'. The paper ends with the case for a robust, research-informed debate about the contested purpose of post-compulsory education in the twenty-first century, the processes of psychological contracting between students and staff in colleges of further education and universities, and how contractual expectations and beliefs change over time.